ChemInform Abstract: Studies on Retro‐[1, 4] Brook Rearrangement of 3‐Silyl Allyloxysilanes. Observation of the Formation of Unusual 3, 3‐Bissilyl Enols. Issue 1 (3rd January 2013) - Gan, Zubao; Wu, Ya; Gao, Lu; Sun, Xianwei; Lei, Jian; Song, Zhenlei; Li, Linjie
Abstract Retro‐[1, 4]‐Brook rearrangement of a wide variety of silyl allyloxysilanes is studied.